When Brokerage Between Friendship Cliques Endangers Trust: A Personality–Network Fit Perspective - Tasselli, Stefano; Kilduff, Martin (Academy of Management Journal, 2018)
Workplace friendship obligations of openness and favoritism are likely to conflict with organizational norms of discretion and neutrality. This dilemma is especially apparent for Simmelian brokers, who divide time and attention across multiple, otherwise disconnected, friendship cliques. In two samples, we found support for the core idea that the fit between the requirements of the network role and the personality of the individual facilitates trust. Simmelian brokers are trusted by their friends if they exhibit a role-appropriate diplomatic personality style involving flexibility of self-presentation (high self-monitoring) and inhibition of verbal loquaciousness (low blirtatiousness). Of course, not everyone engages in Simmelian brokerage. Some individuals experience a strongly cohesive situation—i.e., a single friendship clique within which they are embedded. For these nonbrokers, we hypothesized and found that the most appropriate trait combination likely to maintain the trust of a group of tightly bound colleagues involved a forthright, be-true-to-yourself, loquacious personality style (i.e., low self-monitoring, high blirtatiousness). In introducing a personality–network fit perspective concerning whether Simmelian brokers are trusted by their colleagues, we help reconcile discrepancies in prior literature concerning whether these brokers are paralyzed into indecision by cross-pressures. Brokers who flexibly and guardedly manage individuality facilitate interconnection across cliques.